2014
DOI: 10.1111/jcmm.12157
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of pre‐vascularized urethral patch with muscle flaps and hypoxia‐activated hUCMSCs improves its therapeutic outcome

Abstract: Tissue engineering has brought new hopes for urethral reconstruction. However, the absence of pre-vascularization and the subsequent degradation of materials often lead to the failure of in vivo application. In this study, with the assistance of hypoxia-activated human umbilical cord mesenchymal stem cells (hUCMSCs), pedicled muscle flaps were used as materials and pre-incubated in ventral penile subcutaneous cavity of rabbit for 3 weeks to prepare a pre-vascularized urethral construct. We found that small ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…57 Indeed, vascularization promotion is a well-documented ability characterizing hDPSCs 24,58,59 which does not relate to tumorigenesis, being instead important for regeneration. As formerly demonstrated by Sun et al, 60 vascularization proved to be a favourable condition in supporting the urethral regeneration. The regeneration of muscular component only would provide a transient/temporary recovery of the urinary continence.…”
Section: Discussionsupporting
confidence: 59%
“…57 Indeed, vascularization promotion is a well-documented ability characterizing hDPSCs 24,58,59 which does not relate to tumorigenesis, being instead important for regeneration. As formerly demonstrated by Sun et al, 60 vascularization proved to be a favourable condition in supporting the urethral regeneration. The regeneration of muscular component only would provide a transient/temporary recovery of the urinary continence.…”
Section: Discussionsupporting
confidence: 59%
“…To minimize the potential immune rejection in our study, AMSCs were derived from syngeneic rat donors, not human, but we could speculate that hypoxia pretreatment should produce similar effects on therapeutic function of human AMSCs for ED. Actually, several previous studies have investigated the influence of hypoxic pre-conditioning on therapeutic effects of human ADSCs in other animal model[ 53 , 54 ], and it has been confirmed that hypoxic pre-conditioning can improve the therapeutic effect of human ADSCs.…”
Section: Discussionmentioning
confidence: 97%
“…During the last years, important advances in generation of vascularized tissue engineering have been achieved ( 23 ). However, until today flap surgery still remains the gold standard for plastic-reconstructive treatment of oncological defects ( 24 ). The immediately/simultaneously used transpelvic VRAM flap has several advantages: first of all, the VRAM flap is a very safe and robust flap and relatively easy to technical perform, when necessary plastic-reconstructive expertise exists.…”
Section: Plastic-reconstructive Measures Of Rectal and Anal Carcinomamentioning
confidence: 99%